Haunted empire : Gothic and the Russian imperial uncanny - Sobol, Valeria (NIU series in Slavic, East European, and Eurasian studies., 2020)
"This book shows that Gothic elements in Russian literature (the themes of horror, medieval barbarity, darkness, and transgression) frequently expressed deep-set anxieties about the Russian imperial and national identity"--